Development of a patient-report pressure algometer for the quantification of abdominal examination - Seok-Jae Ko; Keun Ho Kim; Sang Hun Lee; Mi Hong Yim; Jae-Woo Park (Integrative Medicine Research)
Background: Abdominal examination (AE), one of the primary diagnostic tools used in traditional Korean medicine (TKM), has a limitation of being subjective due to depending on individual practitioner's experience. Therefore, we devised a novel patient-report pressure algometer (PA) and performed a clinical trial to investigate its validity. Methods: In total, 44 participants with functional dyspepsia and 44 healthy participants completed the study. The participants were allocated into one of two groups according to the existence of abdominal stiffness at 5 acupoints or abdominal tenderness at 12 acupoints diagnosed by TKM doctors. The pressure depth and pressure pain threshold (PPT) were evaluated using the PA at the same acupoints. We assessed the validity (sensitivity and specificity) of PA and calculated the area under the curve (AUC) and optimal cutoff value of the test variables (pressure depth and PPT) to criterion standards (abdominal stiffness and tenderness). Results: Pressure depth and PPT assessed by PA showed high sensitivity and specificity in diagnosing abdominal stiffness and tenderness. The validity at CV-14 of diagnosing abdominal tenderness with PPT by PA had a sensitivity of 73.1%, specificity of 77.8%, and an AUC of 0.807 with a P value of < 0.001. Conclusion: This study may provide evidence of standardization and quantification of AE through PA.